AAGBS Annual Report 2021: AAGBS KPI & PI achievements (thrust 3) - UiTM, AAGBS (Arshad Ayub Graduate Business School (AAGBS), 2021)
Thurst 3 research, consultancy, publication, student development & alumni by leader Prof. Dr. Norzanah Mat Nor.